2012
DOI: 10.1073/pnas.1117691109
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotope variability of oceanic DMSP generation and its contributions to marine biogenic sulfur emissions

Abstract: Oceanic dimethylsulfoniopropionate (DMSP) is the precursor to dimethylsulfide (DMS), which plays a role in climate regulation through transformation to methanesulfonic acid (MSA) and nonseasalt sulfate (NSS-SO 4 2− ) aerosols. Here, we report measurements of the abundance and sulfur isotope compositions of DMSP from one phytoplankton species (Prorocentrum minimum) and five intertidal macroalgal species (Ulva lactuca, Ulva linza, Ulvaria obscura, Ulva prolifera, and Polysiphonia hendryi) in marine waters. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
59
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 32 publications
(51 reference statements)
9
59
1
Order By: Relevance
“…Even lower δ 34 S of DMSP (+11.3‰) was recorded in a salt marsh on Dauphin Island (SI Appendix, S8). These results demonstrate that there can be a larger variability of δ 34 S in DMSP in estuarine and coastal waters, depending on location and local conditions, as has been shown previously for bulk S isotope analysis of different algae species (15,16) and DMSP of estuarine environments (8). Nevertheless, from a global perspective, the δ 34 S values of DMSP and its volatile breakdown product DMS are likely overwhelmingly dominated by the open ocean DMSP/DMS signature.…”
Section: Significancementioning
confidence: 63%
See 1 more Smart Citation
“…Even lower δ 34 S of DMSP (+11.3‰) was recorded in a salt marsh on Dauphin Island (SI Appendix, S8). These results demonstrate that there can be a larger variability of δ 34 S in DMSP in estuarine and coastal waters, depending on location and local conditions, as has been shown previously for bulk S isotope analysis of different algae species (15,16) and DMSP of estuarine environments (8). Nevertheless, from a global perspective, the δ 34 S values of DMSP and its volatile breakdown product DMS are likely overwhelmingly dominated by the open ocean DMSP/DMS signature.…”
Section: Significancementioning
confidence: 63%
“…Recently, Oduro et al (8) used a multistep extraction of large seawater volumes (e.g., 50 L) coupled with Raney nickel dehydrosulfurization and subsequent fluorination for the S isotope analysis of DMSP in intertidal macroalgae (+17.3 to +19.3‰) and estuarine phytoplankton blooms (+19 to +20‰). However, there are still no direct DMS and DMSP δ 34 S data in oligotrophic oceans owing to their typically low concentrations of 0.5-5 and 5-80 nM, respectively (9).…”
mentioning
confidence: 99%
“…(Norman et al, 1999) and Concordia station (75.1 • S, 123.3 • E; 3233 m a.s.l) . We estimated the amount of biogenic SO Another method for estimating biogenic SO 2− 4 is to use S-isotope ratios (δ 34 S) of SO 2− 4 aerosols, because the δ 34 S values of biogenic DMS (18 ± 2 ‰) are greater than those of anthropogenic SO 2− 4 (5 ± 1 ‰) but less than that of sea salt (21.0 ± 0.1 ‰) (e.g., Wadleigh, 2004;Lin et al, 2012;Oduro et al, 2012). A wide range in δ 34 S (0-8 ‰) has been reported for anthropogenic SO 2 compared with values reported for other sources (Krouse and Grinenko, 1991).…”
Section: Aerosol Particles Formed During Periods Of Arctic Haze (Aprimentioning
confidence: 99%
“…To the best of our knowledge, this is the first report containing S isotopic information on Indian aerosols. Nonetheless, from available literature containing S isotopic composition data from other regions and oceanic realms (Norman et al, 1999;Oduro et al, 2012;Amrani et al, 2013), we showed typical end member values in the Fig. 6 and attempted to provide interpretation for observed δ 34 S values of bulk aerosols over Goa.…”
mentioning
confidence: 99%
“…As Goa is a typical costal locale experiencing strong biogeochemical in the coastal waters just before arrival of monsoon, enhancement of δ 34 S shows most likely tracks changes in the sulfur inventory. Recently Amrani et al (2013) and Oduro et al (2012) have shown oceanic emissions of volatile dimethyl sulfide (DMS) and its precursor, dimethylsulfoniopropionate (DMSP) represent the largest natural source of biogenic sulfur to the global atmosphere, where it mediates aerosol dynamics and may, in turn, affect climate. Amrani et al (2013) reported δ 34 S of DMS and DMSP ranging between +18.9 and +20.3‰, remarkable consistent across the globe.…”
mentioning
confidence: 99%